An additional dimension to health inequalities: disease severity and socioeconomic position. Issue 10 (1st October 1999) - Eachus, J; Chan, P; Pearson, N; Propper, C; Davey Smith, G
Abstract : OBJECTIVE: To investigate the association between the severity of hip pain and disability, and a number of measures of socioeconomic position, using a range of individual and ecological socioeconomic indicators. DESIGN: Interviewer administered and self completed questionnaires on symptoms of pain and disability, general health and socioeconomic indicators, completed by people reporting hip pain in a cross sectional, postal, screening questionnaire. SETTING: 40 general practices from inner city, suburban and rural areas of south west England. PARTICIPANTS: 954 study participants who had reported hip pain in a postal questionnaire survey of 26, 046 people aged 35 and over, selected using an age/sex stratified random probability sample. DATA: Individual indicators of socioeconomic position: social class based on occupation, maximum educational attainment, car ownership, gross household income, manual or non-manual occupation and living alone. Area level measures of socioeconomic position: Townsend scores for material deprivation at enumeration district level; urban or rural location based on the postcode of residence. Severity of hip disease, measured by the pain, disability and independence components of the New Zealand score for major joint replacement. Self reported comorbidity validated using general practice case notes and summary measures of general health. MAIN RESULTS: Increasing disease severity was strongly associated with increasing age and a variety of measures of general health, including comorbidity. The data provide considerable evidence for the systematic association of increased severity of hip disease with decreasing socioeconomic position. Measures of socioeconomic position that were systematically associated with increasing disease severity, standardised for age and sex, included educational attainment (relative index of inequality 1.95 (95% confidence intervals 1.29 to 2.62) and income (relative index of inequality 4.03 (95% confidence intervals 3.43 to 4.64). Those with access to a car (mean disease severity 15.5) had statistically significant lower severity of hip disease than those without (mean 17.5, p < 0.01). Similar results were found for access to higher or further education and living with others. For a given level of income, people with greater comorbidity had more severe hip pain and disability. The gradient in disease severity between rich and poor was steepest among those with the most comorbidity. CONCLUSIONS: People with lower socioeconomic position experience a greater severity of hip disease. The poorest sector of the population seem to be in double jeopardy: they not only experience a greater burden of chronic morbidity but also a greater severity of hip disease. This study has implications for health care provision, if the National Health Service is to live up to its principle of equal treatment for equal medical need.